Social and health integration policies and the right of the regions - Buzzanchi, Camilla (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The Law & Innovation in Public Administration Observatory of the University of Milan Bicocca, a centre for the study of new regulations in the public sector, has dedicated its first Annual Report for 2022 to the theme of social and health integration: hence to that complex of policies, whose constitutional framework is provided by articles 32 and 38, which elevate the right to health protection and the social security system to pivotal elements of the form of welfare state outlined by the fundamental norm. The public action under consideration is based on a broad commitment of the territorial administrations towards these welfare objectives: it is to the regions and municipalities, as well as to private subjects involved in planning and delivery, that the republican order entrusts health and assistance policies.